PENINGKATAN KAPASITAS PRODUKSI AKUAKULTUR PADA PEMELIHARAAN IKAN SELAIS (Ompok sp) SISTEM AQUAPONIK - Putra, Iskandar; Pamukas, Niken Ayu; Rusliadi, Rusliadi (Jurnal Perikanan dan Kelautan, 2013)
Aquaponics, the combined culture of fish and plants in recirculating systems,hasbecome increasingly popular. Ammonia that excreted from fish metabolic activity is aserious problem in intensive aquaculture production systems because it would build-upto toxic level in fish tanks. Therefore, recirculating system with filtration process be-comes an important component to maintain water quality in order to be an appropriatecondition for fish production. The purpose of this study was to develop a silais (Ompoksp) by increasing production capacity with intensive Aquaculture of high density ismaintained in the media filter reisrkulasi Chinese Cabbages (aquaponics system). Theresult of the experiments showed silais fish farming (Omphok sp) aquaponics system toincrease production capacity to produce biomass of fish silais to 0.878 kgs and Chi-nese Cabbages up to 1.161 kgs and fish performance of that system such as survivalrate and food conversion ratio, were higher than the others, i.e., 100 % and 1.24, re-spectively. However, fish specific growth rate of the treatment (2,15 %) have no sig-nificant difference (P> 0.05) compared to other treatmen.